Deciphering the Paradoxical Nature of Ascorbic Acid in Musca domestica Larvae - Dhage, Prajakta A.; Sharbidre, Archana A. (Chemistry and Biochemistry: Research Progress Vol. 1, 2025)
Aims: The purpose of this study is to evaluate the pro-oxidant and antioxidant properties of ascorbic acid (AA) in Musca domestica larvae Study Design: The study design involved assessing the pro-oxidant properties of M. domestica larvae by exposing them to different dosages of AA. Additionally, the antioxidant capacity was evaluated through biochemical assays conducted on both normal larvae and those challenged with D-galactose (D- gal). Place and Duration of Study: Department of Zoology, Savitribai Phule Pune University, Pune between June 2009 and July 2010. Methodology: The M. domestica larvae were subjected to different doses of AA to access the pro-oxidant nature. This study also investigated the antioxidant properties of AA in the D- gal induced oxidative stress condition by assessing the parameters as biochemical assays (Superoxide dismutase, Catalase, Glutathione S transferase, Lipid peroxidation and Protein carbonylation)and larval survival post-treatment with AA and D- gal. Results: A notable association was seen between larval mortality and AA concentration, with optimal survival at 20 mM and complete mortality at 100 mM, due to AA's pro-oxidant properties. At a dosage of 10 mM, AA considerably mitigated the oxidative stress generated by D-gal (p < 0.05) and preserved both pupal survival and eclosion rates. Conclusion: The transitional behavior of AA in M. domestica larvae is concentration-dependent, with reduced concentrations improving survival rates and higher concentrations resulting in increased mortality, underscoring the necessity for meticulous dose evaluation before administration in biological systems.